Dynamical Simulation of a CNC Turning Centre: Survey Paper - Alzghoul, Mohammad; Szilágyi, Attila (Design of Machines and Structures, 2020)
This paper shows the most common rotor systems which can be used to analyse a CNC turning center. Starting with the simplest rotor system representation (single-degree-of-freedom) up to analysing multi-degree-of-freedom and infinite-degree-of-freedom rotor systems using the TMM (Transfer Matrix Method) when it comes to cases like multi desk rotors and Jeffcott-rotors.